The Solvatomagnetism of Et(33) Betaine and of Its Phenolic Precursor - Caroli-Rezende, M; Martinez-Gomez, F; Rodriguez-Huenchun, V (John Wiley and Sons Ltd, 2024)
The 1H and 13C NMR spectra of the N-(3,5-dichloro-4-hydroxyphenyl)- 2,4,6-triphenylpyridinium perchlorate and of its deprotonated betaine 4-(2,4,6-triphenylpyridinio)-2,6-dichlorophenolate (Wolfbeis s ET(33) dye) were recorded in various solvents and analyzed in search of solvent-dependent shifts that characterize their solvatomagnetism, which was compared with the well-known UV–vis spectral behavior of this important solvatochromic dye. Although the NMR spectra of ET(33) and its phenolic precursor in different solvents correlated only poorly with their UV–vis spectral responses, they provided valuable information on specific structural features and solute–solvent interactions that are not available from their UV–vis spectra. © 2024 John Wiley & Sons Ltd.